Floodplain meadow partnership: A working model of effective communication between practitioners, academics and policymakers. Issue 2 (25th June 2021) - Rothero, Emma; Tatarenko, Irina; Jefferson, Richard; Skinner, Ann; Wallace, Hilary; Gowing, David; Clarke, Stewart; Johnson, Matt; Davies, Gareth
Abstract: The article describes a model system for facilitating the transfer of knowledge between researchers and practitioners. The system described has a focus on a single habitat, floodplain meadows, and a case is made for replicating the model for other habitats. Even a single habitat has a wide variety of stakeholders, but a focused partnership with representation across the stakeholder community can prove a useful vehicle for disseminating knowledge and best practice. The structure of the partnership is set out from a steering group to local representatives, and the division of tasks between specialists is explained. The partnership is UK‐based and UK‐focused, yet has an international dimension. The longevity of the partnership and the intensity of interaction with stakeholders are concluded to be important and suggested as a model for others to follow. Abstract : The Floodplain Meadow Partnership offers a model of academic‐practitioner‐policy working that brings a focus to a specific habitat floodplain meadows. The FMP is steered by a wide range of organisations all with an interest in, and influence over, floodplain meadows in the UK. The Steering Group visited the Outer Hebrides in 2018 to explore the wet grasslands. Photo credit: Mike Dodd.